The teaching internship and educational training in accounting: Teaching competencies acquired in post-graduation - Layne Vitória Ferreira; Edvalda Araújo Leal (Arizona State University, 2020)
The study aims to identify, in the perception of postgraduate students in stricto sensu Programs in Accounting Sciences (PPGCCs) in Brazil, which competencies are developed in the teaching internship for teaching qualification. The research, with a quantitative approach, had a sample of 296 students who completed the teaching internship between 2013 and 2017. Through exploratory factor analysis, the identified factors explained 71.41% of the variation in the data, indicating a high degree of agreement among the post-undergraduates regarding the teaching skills development in the teaching internship. The identified factors were: Factor 1 - "Competences on Reflection, Research, Planning and Communication in teaching"; Factor 2 - "Skills for Planning, Content Preparation and Application of New Technologies"; and Factor 3 - "Competences in the Evaluation, Organization and Development of Teaching Methodologies". The contribution of the teaching internship is verified providing that theoretical knowledge and teaching practice can be associated by the student, favoring the necessary skill development for teaching. The study makes it possible to improve the teaching internship, highlighting the need for the guidelines that guide it and clear educational goals, as well as the importance of the student's supervision by the professor who guides this process.